Response of linseed (Linum usitatissimum) to sulphur, zinc and iron under irrigated conditions: Response of linseed (Linum usitatissimum) to sulphur, zinc and iron under irrigated conditions - B M WAKCHAURE,; P N KARANJIKAR,; V G TAKANKHAR, (Journal of Oilseeds Research, 2020)
An experiment was conducted at College of Agriculture, Latur during rabi 2018-19 to study the response of linseed to macro and micro nutrients. Application of RDF + ZnSO4 @ 20 kg/ha + FeSO4 @ 20 kg/ha was found most effective for increasing growth and productivity of linseed. Application of RDF in combination with ZnSO4 @ 20 kg/ha and FeSO4 @ 20 kg/ha recorded significantly higher growth and yield attributing characters and seed yield (1998 kg/ha), straw yield (2204 kg/ha), oil yield (476 kg/ha), gross monetary return (`71,880/ha), net monetary return (`36,426/ha) and B:C ratio (2.03) of linseed than RDF alone or in combination with ZnSO4, FeSO4 or sulphur alone respectively.